2017
DOI: 10.1111/dth.12575
|View full text |Cite
|
Sign up to set email alerts
|

Styling without shedding: Novel topical formula reduces hair shedding by contracting the arrector pili muscle

Abstract: Approximately 40% of women experience excessive hair shedding during styling (e.g., hair brushing). Previously, we demonstrated that topically applied phenylephrine, a potent α adrenergic receptor agonist, can be used to contract the arrector pili muscle of the follicular unit; thus, increasing the force required to pluck hair and reducing shedding during brushing. While demonstrating efficacy, phenylephrine has several drawbacks when applied to the scalp, including the possibility cardiovascular events. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These data indirectly provide evidence of the expression of TAAR receptors in the arrector pili muscle. Additionally, the TAAR agonist shampoo showed similar efficacy to the synephrine hydrochloride solution previously tested in reducing shedding during brushing. The average reduction was 31% for the cohort with a maximum reduction of 77%.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…These data indirectly provide evidence of the expression of TAAR receptors in the arrector pili muscle. Additionally, the TAAR agonist shampoo showed similar efficacy to the synephrine hydrochloride solution previously tested in reducing shedding during brushing. The average reduction was 31% for the cohort with a maximum reduction of 77%.…”
Section: Discussionmentioning
confidence: 76%
“…To date, no treatment is available for the reduction of hair shedding caused by the mechanical stress of everyday washing and styling. Previously, our group demonstrated that a solution containing synephrine hydrochloride significantly reduced hair shedding during brushing . Unfortunately, due to the high concentration of the weak agonist required to affect the arrector pili muscles in hair follicles, development of a shampoo with synephrine hydrochloride was not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations